Phenyl-Linked Anthracene-Based Macrocycles with Geometrically Tunable Optical Properties - Rong, Ming-Guang; Wang, Junting; Low, Kam-Hung; Liu, Junzhi (Organic Materials, 2020)
Anthracene has been widely explored because of its intrinsic photophysical and photochemical properties. Here, two novel anthracene-based macrocycles (1 and 2) were designed and synthesized with para- and meta-phenylene spacers. X-ray crystallographic analysis demonstrates that compound 1 with para-phenylene spacers adopts a nearly planar structure, while compound 2 with meta-phenylene spacers displays a V-shaped geometry. The photophysical properties of the resultant macrocycles, which are structural isomers, are well studied using photoluminescence spectra and time-resolved absorption spectra, which are further corroborated by density functional theory calculations. The optical properties of these two novel macrocycles can be finely tuned via their geometries.
Keywords: anthracene; macrocycles; geometrically; optical properties; fluorescence